Perineal protection methods: knowledge and use - Martínez, Esther María López; Sáez, Zaraida Avilés; Sánchez, Encarnación Hernández; Ávila, Marcos Camacho; Conesa, Ester Marín; Ferrer, María Belén Conesa (Revista da Escola de Enfermagem da USP, 2021)
Objective: To analyse the knowledge and use of perineal protection methods during the expulsive stage by health professionals involved in childbirth and whether they correspond to the World Health Organization’s recommendations. Method: This was a cross-sectional descriptive study aimed at health workers involved in births in Spain. Results: Fifty-seven professionals participated in the study: midwives (47%), gynaecologists (25%), nurse residents (14%) and resident physicians (14%) in obstetrics and gynaecology. The degree of knowledge and use of perineal protection methods differed according to the position held and was very limited among gynaecologists and resident physicians. The only method recognized by all positions was “hands on” (p = 0.05). “Hands off ” (p = 0.002), “delayed pushing” (p = 0.0001) and “maternal posture” (p = 0.03) were only known to midwives and nurse residents. “Flexion technique” (p = 0.035) and “delayed pushing” (p = 0.011) were used effectively by midwives and nurse residents. “Episiotomy” was erroneously identified as a method to protect the perineum by gynaecologists and resident physicians (p = 0.003). Conclusion: The degree of knowledge and use of perineal protection methods by health care professionals does not correspond to the recommendations of the World Health Organization.